TOXICITY AND EFFICACY OF TYROSINE KINASE INHIBITORS IN COMBINATION WITH CHEMOTHERAPY IN PATIENT WITH RESISTANT Ph-POSITIVE ACUTE LYMPHOBLASTIC LEUKEMIA (CASE REPORT AND LITERATURE REVIEW) - K. I. Zarubina; E. N. Parovichnikova; O. A. Gavrilina; A. N. Sokolov; V. V. Troitskaya; L. A. Kuzmina; V. E. Mamonov; G. M. Galstyan; V. G. Savchenko (Онкогематология, 2017)
A wide range of toxic complications of BCR-ABL tyrosine kinase inhibitors therapy due to non-targeted inhibition of other protein kinases. This is of particular importance in the treatment of patients with Ph-positive lymphoblastic leukemia, who receive, in addition to tyrosine kinase inhibitors, cytotoxic drugs, enhancing myelotoxicity and, as a consequence, infections and thrombo-hemorrhagic complications. In addition, complex inter-drug interactions lead to the manifestations of combined toxicity. This article presents a case report of patient with relapsed acute Ph-positive lymphoblastic leukemia, treatment of which was accompanied by numerous complications, especially during treatment of II and III generation tyrosine kinases inhibitors.